Qingjie Fuzheng Granule Inhibited the Migration and Invasion of Colorectal Cancer Cells by Regulating the lncRNA ANRIL/let-7a/TGF-β1/Smad Axis. (29th June 2020) - Zhang, Ling; Liu, Jianxin; Lin, Shan; Tan, Jingzhuang; Huang, Bin; Lin, Jiumao
Abstract : Qingjie Fuzheng granule (QFG) promotes cancer cell apoptosis and ameliorates intestinal mucosal damage caused by 5-fluorouracil. However, the antitumor role of QFG in colorectal cancer (CRC) progression remains unclear. In this study, the growth of HCT-8 and HCT116 cells incubated with various concentrations of QFG for 24 and 48 h was evaluated using MTT assays; their abilities of migration and invasion were investigated through wound healing and Transwell assays. The expression of lncRNA ANRIL, let-7a, and the TGF- β 1/Smad signaling pathway components was assessed using real-time PCR and western blotting. The results elicited that QFG significantly suppressed the growth of HCT-8 and HCT116 cells; the half-maximal inhibitory concentrations (IC50 ) of QFG for HCT-8 and HCT116 cells for 48 h were 1.849 and 1.608 mg/mL, respectively. The abilities of wound healing, migration, and invasion of HCT-8 and HCT116 cells were dose-dependently decreased by QFG treatment for 24 h, respectively. QFG decreased the expression of lncRNA ANRIL, TGF- β 1, phosphorylated (p)-Smad2/3, Smad4, and N-cadherin and upregulated the expression of let-7a in HCT-8 and HCT116 cells. Collectively, our data demonstrated that QFG inhibited the metastasis of CRC cells by regulating the lncRNA ANRIL/let-7a/TGF- β 1/Smad axis, indicating that they might serve as an adjunctive medicine for CRC treatment.